Pengembangan Industri Kreatif di Desa Wisata Bona, Belega dan Keramas Perspektif Gender - Mahyuni, Ida Ayu Putu (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 20 No 2 (2020), 2020)
This study on the development of creative industries with a gender perspective is expected to know and understand about the participation of women workers for family income in order to improve their welfare through the industrial sector. as well as the efforts that have been made by related parties, such as the community, local government, and parties concerned about the need to uphold justice in improving the quality of life of the population, especially women. The main problem is: What factors cause women to choose to work and be involved in the creative industry? What are the parties involved in upholding justice in improving the quality of life of the population, especially women according to the gender responsive Presidential Instruction Number 9 of 2000? Gender analysis is used in this study with the assumption that both men and women work and participate according to their potential and needs and equally get benefits